2017
DOI: 10.1073/pnas.1701425114
|View full text |Cite
|
Sign up to set email alerts
|

Healthy offspring from freeze-dried mouse spermatozoa held on the International Space Station for 9 months

Abstract: If humans ever start to live permanently in space, assisted reproductive technology using preserved spermatozoa will be important for producing offspring; however, radiation on the International Space Station (ISS) is more than 100 times stronger than that on Earth, and irradiation causes DNA damage in cells and gametes.Here we examined the effect of space radiation on freeze-dried mouse spermatozoa held on the ISS for 9 mo at -95°C, with launch and recovery at room temperature. DNA damage to the spermatozoa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 47 publications
1
59
0
2
Order By: Relevance
“…Japan Aerospace Exploration Agency (JAXA) has conducted a series of monitoring experiments to evaluate the radiation environment inside and outside the Japanese Experiment Module Kibo, which is part of the ISS with Passive Dosimeter for Life-Science and Experiments in Space (PADLES) [9,13,14]: area radiation monitoring in the Japanese Experiment Module "Kibo" of the ISS (Area PADLES) [15]; dose measurements of biological samples exposed to space radiation (Bio PADLES) [16][17][18][19]; radiation dosimetry of Asian astronauts (Crew PADLES); various kinds of international cooperative experiments with ISS partners (Dosimetric-PADLES); measurement of the directional dependence of the radiation dose inside the Kibo module (Exp PADLES) [11,20]; and measurement of outside doses and evaluation of the shielding effect of the ISS Kibo hull (Free-space PAD-LES). Those experiments were initiated in 2008 just after attachment of the Japanese Pressurized Module (JPM) to the ISS.…”
Section: Radiation Environment In Low-earth Orbits (Leo)mentioning
confidence: 99%
See 3 more Smart Citations
“…Japan Aerospace Exploration Agency (JAXA) has conducted a series of monitoring experiments to evaluate the radiation environment inside and outside the Japanese Experiment Module Kibo, which is part of the ISS with Passive Dosimeter for Life-Science and Experiments in Space (PADLES) [9,13,14]: area radiation monitoring in the Japanese Experiment Module "Kibo" of the ISS (Area PADLES) [15]; dose measurements of biological samples exposed to space radiation (Bio PADLES) [16][17][18][19]; radiation dosimetry of Asian astronauts (Crew PADLES); various kinds of international cooperative experiments with ISS partners (Dosimetric-PADLES); measurement of the directional dependence of the radiation dose inside the Kibo module (Exp PADLES) [11,20]; and measurement of outside doses and evaluation of the shielding effect of the ISS Kibo hull (Free-space PAD-LES). Those experiments were initiated in 2008 just after attachment of the Japanese Pressurized Module (JPM) to the ISS.…”
Section: Radiation Environment In Low-earth Orbits (Leo)mentioning
confidence: 99%
“…We concluded that the characteristics of the space radiation environment in LEO contain the following: (i) a high contribution from high-linear energy transfer (LET) radiation that have a high-quality factor (QF) up to 30; (ii) dose rates have values that are a few hundred times greater than those on the ground; (iii) the directional distribution of space radiation is nearly isotropic; and (iv) radiation effects occur under μG [13,14,19]. Space radiation for LET greater than several keV/μm causes more serious damage to living things than low-LET radiation.…”
Section: Radiation Environment In Low-earth Orbits (Leo)mentioning
confidence: 99%
See 2 more Smart Citations
“…Blastocyste immunofluorescence staining was performed as described to evaluate the quality of blastocysts derived from mPLCζ or ePLCζ mRNA injected embryos [30]. The primary antibodies used were an anti-CDX2 rabbit monoclonal antibody (1:500; BioGenex, California, CA, USA) to detect the TE cells and an anti-NANOG mouse polyclonal antibody (1:500; Abcam, Cambridge, UK) to detect the ICM cells.…”
Section: Blastocyst Immunostainingmentioning
confidence: 99%